1997
DOI: 10.1074/jbc.272.23.15036
|View full text |Cite
|
Sign up to set email alerts
|

The T Cell-directed CC Chemokine TARC Is a Highly Specific Biological Ligand for CC Chemokine Receptor 4

Abstract: Chemokines are small secreted polypeptides that play important roles in a wide range of inflammatory and immunological processes by recruiting selected subsets of leukocytes (1, 2). The known chemokines are divided into two major subfamilies based on the spacing of the first two cysteines in the conserved motif. The CXC chemokine subfamily, which includes IL-8 1and IP-10 (4), is characterized by the presence of a single amino acid separating the first two cysteines. The two cysteines are adjacent in the CC che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
398
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 510 publications
(419 citation statements)
references
References 67 publications
15
398
1
1
Order By: Relevance
“…CCR4 binds CCL2, -3, -5, -17 and -22 [26,28]. However, other reports have shown that CCL17 and -22, but not CCL2, -3 and -5 are specific functional ligands for CCR4 [29][30][31]. Thus, CCL2 binding to CCR4, as indicated by our results obtained in the reconstruct (Table 5) and Transwell (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…CCR4 binds CCL2, -3, -5, -17 and -22 [26,28]. However, other reports have shown that CCL17 and -22, but not CCL2, -3 and -5 are specific functional ligands for CCR4 [29][30][31]. Thus, CCL2 binding to CCR4, as indicated by our results obtained in the reconstruct (Table 5) and Transwell (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…In our view, CD4 þ T-cells are likely to be recruited from the peripheral blood to lymph nodes infiltrated by classical Hodgkin lymphoma via cytokines such as TARC and RANTES/CCL5 secreted by the Hodgkin-and Reed-Sternberg cells. 16 Interestingly, although only CD4 þ T-cells express CCR4, 17 both CD4 þ T-cells and macrophages express CD4 and CCR5. Although HIV-infected CD4 þ T-cells are eliminated in high numbers, macrophages usually persist as viral reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…Northern blots were prepared as described previously (24). Briefly, total RNAs were prepared from various cell lines using Trizol (Life Technologies).…”
Section: Northern Blotmentioning
confidence: 99%
“…Briefly, to express fractalkine-SEAP, the DNA fragment encoding fractalkine was amplified from fractalkine cDNA by PCR using 5Ј SalIfractalkine primer (ϩ5Ј-CGCGTCGACTCAGCCATGGCTCCGATA TCT-3Ј) and 3Ј fractalkine-XbaI primer (Ϫ5Ј-CGCTCTAGAGGTGGCT GCCTGGGCGTCAGG-3Ј) and subcloned into pDREF-SEAP (His)6-Hyg vector as described previously (24). CX 3 CSEAP was similarly generated using 5Ј SalI-fractalkine primer and 3Ј fractalkine-XbaI-2 primer (Ϫ5Ј-CGCTCTAGATAGGGCAGCAGCCTGGCGGTC-3Ј).…”
Section: Production Of Recombinant Proteinsmentioning
confidence: 99%
See 1 more Smart Citation